Resource Analysis in Indonesia Textile Industry: “A Development of Industrial Data Analytic Framework” - Saroso, Hardijanto -; Lasmy, Lasmy; Syahchari, Dicky Hida; Herlina, Maria Grace; Sudrajat, Darjat (International Journal of Supply Chain Management, 2020)
— The future trend in the field of management is the increasingly applied analytic data in every management decision, both for development and investment. Data submitted by companies are processed and evaluated by investors. However, the calculation pattern that is done is still based on financial analysis. This paper is intended to develop an analytic data framework that can be used by CEOs or investors in managing and valuing an industry. The research methodology used is using historical data in the Company's annual reports for the past five years and calculate it using SEM-PLS. This data is then entered into the analytic data framework and then being evaluated to get the essential resources or critical processes that have a strategic position or value in the industry. This research is using textile industry data. In the textile industry, it is found that the critical strategic resources are raw materials that significantly affect the Company's performance. This key finding is in line with the development of technology in raw material in the textile industry. This analysis method is intended to complement existing financial-based analyses that has been done for a long time. With this new analysis framework, the CEO and Investor will get a new perspective on the industry and take advantage of additional information from its result.